METHODS AND APPROACHES FOR DEVELOPING NATIONAL AND GENERAL CULTURAL COMPETENCES IN STUDENTS THROUGH EXAMPLES OF ARTISTIC WORKS (Universal International Scientific Journal, 2026)
This article discusses the methods and techniques for instilling national and general cultural competencies in students based on modern approaches in the educational process, and for forming national values ​​and national thinking through works of art.
Keywords: Literary thought; education; modern methods